Cities, Autonomy, and Decentralization in Japan (Routledge, 2006)
Adding a new perspective to the current literature on decentralization in Japan, Cities, Autonomy and Decentralization in Japan, approaches the subject from an urban studies and planning approach. The essays in the collection present a cogent compilation of case studies focusing on the past, present and future of decentralization in Japan. These include small scale development in the fields such as citizen participation (machizukuri), urban form and architecture, disaster prevention and conservation of monuments.